Fertility, Conjuncture, Difference Anthropological Approaches to the Heterogeneity of Modern Fertility Declines - Kreager, Philip; Bochow, Astrid (Berghahn Books, 2017)
In the last forty years anthropologists have made major contributions to understanding the heterogeneity of reproductive trends and processes underlying them. Fertility transition, rather than the story of the triumphant spread of Western birth control rationality, reveals a diversity of reproductive means and ends continuing before, during, and after transition. This collection brings together anthropological case studies, placing them in a comparative framework of compositional demography and conjunctural action. The volume addresses major issues of inequality and distribution which shape population and social structures, and in which fertility trends and the formation and size of families are not decided solely or primarily by reproduction.